الأفعال الإنجازيّة في رسوم متحركة الحسين ابن سينا (دراسة تحليلية تداولية) - Arumsari, Dewi Aisyah Lailatul; Agusti Nurqoiri, Abdi (Al-Uslub: Journal of Arabic Linguistic and Literature, 2025)
In this thesis the author discusses the illocutionary speech acts in the cartoon film Al-Hussein Ibn Sina. The aims of this study are: 1) To find out the types of speech acts (illocutions) in the cartoon film of Al-Hussein Ibn Sina. 2) To find out the purpose in the film. This research is library research. This study uses a descriptive method with a qualitative approach, and the source of data in this study is the speech act in the film Al-Hussein Ibn Sina, the researcher uses in-depth observation and documentation techniques.By using this method, it can be concluded that the results of this study: 1) The illocutionary speech acts in the cartoon film Al-Hussein Ibn Sina amount to 76 utterances while the assertive is 17, the directive is 17, the commissive is 14, the expressive is 19, and the declarative is 9. 2) The purpose of illocutionary speech acts in the cartoon film Al-Hussein Ibn Sina while assertive speech contains explanations, opinions, proposes, affirms, and complains. The directive contains advice/recommendations, orders, prohibitions, requests, expectations. Commissive contains denial, promise, threat, guarantee. Expressives contain anger, sadness, gratitude, sorry, surprise, ridicule, praise, amazement.